Thinking Otherwise about Animals: Review of Nik Taylor and Tania Signal, eds. Theorizing Animals: Re-thinking Humanimal Relations - Kendall-Morwick, Karalyn (Humanimalia, 2012)
Nik Taylor and Tania Signal (Eds.), Theorizing Animals: Re-thinking Humanimal Relations. Brill: Leiden, The Netherlands, 2011. 293 pp. $121.00.